Transformative Effect of ChatGPT on Accounting Education : A New Era AI Chatbot - Filasari, Inta Novia Eka; Suranto, Suranto (Universitas Pendidikan Mandalika, 2025)
This study aims to explore the transformative effects of using ChatGPT on student competence in the future. This study used a qualitative research method with a purposive sample, namely Accounting Education students at Muhammadiyah University of Surakarta. Data was collected through in-depth interviews, classroom observations, and documentation. Researchers applied data triangulation techniques using a thematic analysis approach, namely through the stages of data reduction, data presentation, and conclusion drawing. The results showed that ChatGPT became a popular tool, providing great benefits in improving the efficiency and accessibility of information. Students appreciated ChatGPT's ability to help them complete tasks and provide them with quick answers. However, other issues found in this study include concerns about data accuracy and possible over-reliance on the technology. It is necessary to facilitate the responsible use of ChatGPT and ensure that students retain the ability to solve complex problems and think independently.